Pengaruh Financial Literacy dan Lifestyle Terhadap Personal Finance - Vinka Khoerunnisa Alifa Putri; Azib; Nadia Meirani (Bandung Conference Series: Business and Management, 2023)
Abstract. The current generation in Indonesia is more modern, previously known as the older generation and the younger generation based on the year of birth. Now the generation in Indonesia is dominated by generation Z as evidenced by the highest percentage, namely 27.94%, the second is the millennial generation of 25.87%, the third generation of X is 21.88%, the fourth generation of Baby Boomers is 11.56%, and Post generation Z with the least percentage of 10.88%. With the characteristics of generation Z, there are many skills that need to be possessed by generation Z, one of which is managing personal finances. This research was conducted with the aim of examining the effect of financial literacy and lifestyle on personal finance generation Z in Bandung City Colleges. The method used in this research is descriptive verification method with data analysis techniques using quantitative methods. The population in this study was 669,193.5 people, while the number of samples obtained was 180 Z generations at Bandung City Colleges. The data collection technique used was by distributing questionnaires to generation Z at Bandung City Higher Education. The results showed that financial literacy has a partially significant effect on personal finance, lifestyle has a partial significant effect on personal finance, and simultaneously financial literacy and lifestyle have an effect on personal finance for generation Z in Bandung City Colleges. Abstrak. Generasi di Indonesia sekarang sudah lebih modern yang sebelumnya dikenal dengan generasi tua dan generasi muda berdasarkan tahun kelahiran. Kini generasi di Indonesia didominasi oleh generasi Z yang dibuktikan dari jumlah persentasi terbanyak yaitu 27,94%, yang kedua ada generasi milenial sebanyak 25,87%, yang ketiga generasi X sebanyak 21,88%, keempat generasi Baby Boomer sebanyak 11,56%, dan Post generasi Z dengan persentase paling sedikit yaitu 10,88%. Dengan karakterisik generasi Z sekarang banyak keterampilan yang perlu dimiliki oleh generasi Z salah satunya adalah dalam mengelola keuangan pribadi. Penelitian ini dilakukan dengan tujuan untuk menguji pegaruh financial literacy dan lifestyle terhadap personal finance generasi Z di Perguruan Tinggi Kota Bandung. Metode yang digunakan dalam penelitian ini adalah motode deskriptif verifikatid dengan teknik analisis data menggunakan metode kuantitaif. Populasi dalam penelitian ini sebanyak 669.193,5 jiwa, sedangkan jumlah sampel yang diperoleh sebesar 180 generasi Z di Perguruan Tinggi Kota Bandung. Teknik pengumpulan data yang digunakan dengan mengebarkan kuesioner kepada generasi Z di Perguruan Tinggi Kota Bnadung. Hasil penelitian menunjukkan bahwa financial literacy berpengaruh siginifikan secara pasial terhadap personal finance, lifestyle berpengaruh signifikan secara parsial terhadap personal finance, dan secara simultan financial literacy dan lifestyle berpengaruh terhadap personal finance generasi Z di Perguruan Tinggi Kota Bandung.